Spherical Cubic Bi-Ideals of Gamma Near-Ring - Chinnadurai, V.; Shakila, V. (Communications in Mathematics and Applications, 2021)
The purpose of the article is to study about spherical cubic sets and spherical cubic bi-ideals of Gamma near-ring \(\mathcal R\). We define spherical internal and external cubic sets and their properties. We discuss P-order and \(\mathcal R\)-order, P-union, P-intersection, \(\mathcal R\)-union and \(\mathcal R\)-intersection of spherical cubic sets. We define spherical cubic bi-ideals of gamma near-ring \(\mathcal R\) and prove that P-union, P-intersection, \(\mathcal R\)-union and \(\mathcal R\)-intersection of spherical cubic bi-ideals of Gamma near-ring \(\mathcal R\) are also spherical cubic bi-ideals of Gamma near-ring \(\mathcal R\).